MARKET EQUILIBRIUM IN MICROECONOMICS AND FACTORS AFFECTING ITS CHANGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This paper analyzes the key and modern factors influencing market equilibrium and its changes in microeconomics. The processes of equilibrium formation and disruption are examined based on the demand and supply model. The impact of factors such as household income, consumer preferences, prices of substitute and complementary goods, government policies, taxes, subsidies, and price controls is discussed. In addition, modern factors such as global supply chains, inflation, digital platforms, and information asymmetry are also analyzed. The results show that market equilibrium is a constantly changing process.